CALL: Using, Learning, Knowing, EUROCALL Conference, Gothenburg, Sweden, 22-25 August 2012, Proceedings 2012
DOI: 10.14705/rpnet.2012.000039
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Study on Fluency Among Novice Learners of Japanese

Abstract: The present study examined various aspects of the development of learners' fluency in Japanese using a large set of speech samples collected over a long period, using an online speaking practice/assessment system called Speak Everywhere. The purpose of the present study was to examine: (1) how the fluency related measures changed over time, and (2) which linguistic factors were correlated with each fluency measure. This study used oral production of English-speaking learners enrolled in the first year Japanese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Second, reliable tools for the objective measurement of fluency are readily available and can be utilized across languages (Boersma & Weenink, ). Finally, in regard to measuring oral accuracy and complexity, a number of standards have been created for English (Thai & Boors, 2016) but the same cannot be said for Japanese, especially for Japanese FL learners (Hirotani, Matsumoto, & Fukuda, ). This study focused on the five metrics of fluency that were suggested by Boersma and Weenink () and Hirotani et al ().…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Second, reliable tools for the objective measurement of fluency are readily available and can be utilized across languages (Boersma & Weenink, ). Finally, in regard to measuring oral accuracy and complexity, a number of standards have been created for English (Thai & Boors, 2016) but the same cannot be said for Japanese, especially for Japanese FL learners (Hirotani, Matsumoto, & Fukuda, ). This study focused on the five metrics of fluency that were suggested by Boersma and Weenink () and Hirotani et al ().…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Finally, in regard to measuring oral accuracy and complexity, a number of standards have been created for English (Thai & Boors, 2016) but the same cannot be said for Japanese, especially for Japanese FL learners (Hirotani, Matsumoto, & Fukuda, ). This study focused on the five metrics of fluency that were suggested by Boersma and Weenink () and Hirotani et al (). These factors have been successfully used to judge the fluency of FL learners of Japanese in previous studies (e.g., Hirotani et al, ; Matsushita, ) and include the number of syllables spoken, the number of pauses, the speech rate (number of syllables spoken per second), the articulation rate (number of syllables per phonation time), and the average syllable duration (ASD—speaking time per syllable).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Although one might expect a task‐related practice effect with regard to fluency, the second self‐introductions were not mere repetitions of the first as they were substantially revised. Moreover, no study of L2 learners in formal classroom settings to date has found significant improvement in general spoken fluency in such a short timeframe (see, e.g., Hirotani, Matsumoto, & Fukada, ; Segalowitz & Freed, ).…”
mentioning
confidence: 99%
“…"The basic measures of fluency are the rates (in time) of the production of spoken linguistic units, like words per minute" (Bernstein et al, 2010(Bernstein et al, : p. 1241. Five metrics of fluency have been identified by Hirotani et al (2012) in their study to observe the fluency of learners studying Japanese as a Foreign Language (JFL) and these factors include the number of syllables spoken, the number of pauses, the speech rate number of syllables spoken per second, the articulation rate number of syllables per phonation time, and the Average Syllable Duration (ASD)-speaking time per syllable (Spring et al, 2019).…”
Section: Fluencymentioning
confidence: 99%